Diversity, contestation, participation in Aotearoa New Zealand's multi-use/user marine spaces. (August 2019) - Le Heron, Erena; Logie, June; Allen, Will; Le Heron, Richard; Blackett, Paula; Davies, Kate; Greenaway, Alison; Glavovic, Bruce; Hikuroa, Daniel
Abstract: Coastal nations and islands have featured a participatory turn this century directed to resolving conflicts in multi-use/user marine spaces. Yet, few conceptual and empirical studies focus on participation as an institutional form to engage with the pressures of diverse and contesting uses and user interests in marine environments. These spaces are volatile arenas of power and politics, challenging available regulatory, governance and managerial models. The paper first reviews understandings of the nature of the relational field of diversity-contestation-participation in the international literature and second draws on empirical findings from five case studies of marine participatory process configurations in contemporary Aotearoa New Zealand. The nation is a unique ecological, political, social, cultural and economic setting. Maori (the indigenous people) have developed holistic intergenerational resource nurturing principles and practices (Vision Matauranga (VM)) that are actively shaping marine futures. This momentum has markedly altered the nature and terms of engagement of participation in Aotearoa New Zealand's shallow marine regulatory context. The country is thus an ideal setting to examine the rise of quasi-independent Participatory initiatives, contextualise and examine their diversity, contestation, participation interactions, confront relational and co-production aspects of agency that are an integral part of real-time participatory processes, and to reflect on van Kerkhoff and Lebel's (2015) contention that different possible futures hang on people asking new questions and being brave enough to experiment with process, collaboration, and their own conceptualisations and knowledges'. Highlights: Explores the contention that diversity initiatives enable new questions to be asked. Conceptualises multi-use/user marine spaces as an object of study. Discusses the researchers' commitment to Treaty Partnership research and outlines the generative influences of Vision Matauranga on participation thinking. Reports on pioneering research into diversity initiatives in Participatory Processes. Reflects on the power and politics of implementation prospects.